The effect of in vitro royal jelly provision on adhesion of Pseudomonas aeruginosa - Sifra Kristina Hartono; Tetiana Haniastuti; Heni Susilowati; Juni Handajani; Alma Linggar Jonarta (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Pseudomonas aeruginosa (P. aeruginosa) is an opportunistic bacterium, which could aggressively infect immunocompromised patients and thus, cause high mortality rate. In addition, P. aeruginosa in oropharynx could be aspirated and cause ventilator associated pneumonia. Royal jelly is one of bee’s products that has been used for therapeutic needs including antibacteria. Adherence factor of P. aeruginosa were flagelum, pili and lectin. The aim of the study was to determine the effect of royal jelly to P. aeruginosa adhesion. Suspension of P. aeruginosa (ATCC® 27853) was incubated at 37 °C for 18 h. Treatment groups were exposed to royal jelly with several concentrations, 2%, 4%, 6%; while distilled water was being used as negative control. Bacterial adhesion test was determined using spectrophotometer λ = 600 nm to measure optical density values of adhered bacterial suspension in tubes. The result of one-way ANOVA showed significant differences (p<0.05) of optical density values among groups indicating that royal jelly affected the bacterial adhesion. LSD results showed significant difference of optical density values between 2%, 4%, and 6% royal jelly compared to distilled water. Six percent of royal jelly had the least optical density value compared to the other groups. In conclusion, royal jelly has the ability to decrease adhesion of P. aeruginosa. Six percent of royal jelly has better ability to decrease adhesion of P. aeruginosa than other concentrations.